Self made device by rural Nepalese women for pelvic organ prolapse worn for more than a decade: A constant source of vaginal discharge - Pant, Padam Raj (Nepal Journal of Obstetrics and Gynaecology, 2008)
Complete disappearances of prolapse after the removal of the self made vaginal vaginal devices, made out of sand, jute and fruit seed residue worn for 17-30 years is presented here which speaks of uterovaginal prolapse as gynecological morbidity. Key words: Gynecological morbidity and uterine prolapse.   doi:10.3126/njog.v3i1.1444 NJOG 2008 May-June; 3(1): 58 - 59